Pola Komunikasi Keluarga dalam Pembentukan Karakter Anak - Irham Ritonga; Muhammad Yazid; Lahmuddin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This article discusses the role of family communication in shaping children's character, as it is known that communication is very important in human life, especially in the family. By communicating, people will understand each other. Through communication, people can also share experiences and learn to solve various problems in life. Without communication, it is like living in isolation so that people will not be able to solve the various life problems they experience. Therefore, even though the family is a group with the strongest social ties, if communication within the family does not run smoothly and intensively, then it can certainly greatly affect various matters concerning the development and growth and progress of the family. The results of the study prove that it is true that family communication plays a significant role in improving human resources, especially in terms of children's character building.